Transport of dissolved black carbon from the Prydz Bay Shelf, Antarctica to the deep Southern Ocean. (13th July 2018) - Fang, Ziming; Yang, Weifeng; Chen, Min; Stubbins, Aron; Ma, Haoyang; Jia, Renming; Li, Qi; Chen, Qianna
Abstract: Dissolved black carbon (DBC) is one of the largest pools of molecularly identifiable carbon in the ocean. In the deep ocean, DBC appears to persist for millennia, whereas it can be rapidly degraded by sunlight in surface waters. In Antarctica, the downward transport of dense shelf water (DSW) exports a massive volume of water to the deep Southern Ocean each year. If this sinking DSW is enriched in DBC, it may allow a route for DBC to escape degradation by sunlight in the surface ocean and become sequestered in the deep waters of the global ocean. To investigate this possibility, we quantified dissolved organic carbon (DOC), DBC, and ancillary properties in the waters of an Antarctic shelf sea (Prydz Bay) and adjacent waters. DBC concentrations in Prydz Bay DSW (1.2 ± 0.3 μ mol L −1 ) were elevated compared to those in circumpolar deep water (0.49 ± 0.07 μ mol L −1 ). The water column distribution of DBC in Prydz Bay suggested that sediments were the main source of DBC in DSW. A mixing model incorporating seawater oxygen isotopes (H2 δ 18 O) indicated that Prydz Bay DSW transported DBC and DOC into the deep Southern Ocean. We estimate that the downward transport of DSW from Prydz Bay could contribute 4–9% (66–150 Gg yr −1 ) and 2–4% (3700–8500 Gg yr −1 ) to the DBC and DOC concentrations in Antarctic Bottom Water, respectively. Thus, the downward transport of DBC along the Antarctic shelf/slope is likely a significant source of DBC to the deep waters of the Southern and Global Ocean.